Inequality dimensions of childhood vaccination coverage in Indonesia: a scoping review - Bianda Dwida Pramudita; Jonathan Hasian Haposan; Fulgence Niyibitegeka (Universitas Gadjah Mada, 2026)
Purpose: To map existing evidence on inequalities in childhood immunization coverage in Indonesia using the Social Determinants of Health and PROGRESS-Plus frameworks. Methods: This scoping review included original studies published between 2015 and 2025 that examined inequalities in childhood vaccination coverage in Indonesia. Searches were conducted in PubMed, Scopus, Google Scholar, and Garuda. The review followed PRISMA-ScR with consideration of the PRISMA-Equity extension. Data were charted using a standardized extraction form and synthesized descriptively using narrative and tabular approaches. Results: Of 910 records identified, ten studies met the inclusion criteria. All were cross-sectional, and most used nationally representative data from household surveys or administrative sources (n = 9). Inequalities related to parental socioeconomic characteristics were most frequently examined. No studies assessed disparities related to race, ethnicity, culture, or language, indicating substantial gaps across key equity dimensions. Conclusion: Evidence on childhood vaccination inequalities in Indonesia remains limited in scope and depth. Expanding equity-focused research, particularly on underexplored social and cultural determinants, is essential to support targeted policies and advance equitable immunization coverage in Indonesia.